The future of creativity research: Where are we, and where should we go - Mumford, Michael D.; England, Samantha (Journal of creativity, 2022)
Over the course of the last thirty years, we have made substantial progress in our understanding of creative problem-solving and creative performance. As is always the case, however, progress in our research raises as many new questions as answers. In the present effort, we examine key findings that have emerged in key areas of creativity research including abilities, creative problem-solving processes, creative thinking skills, personality, social interactions, work climate, and environmental context. In each area we examine new questions arising from prior research. Directions for future research on creative performance are also discussed.